Yawn contagion in domestic pigs (Sus scrofa) - Norscia, Ivan (Sci Rep, 2021)
Contrary to spontaneous yawning—an ancient phenomenon common to vertebrates—contagious yawning (elicited by others’ yawns) has been found only in highly social species and may reflect an emotional inter-individual connection. We investigated yawn contagion in the domestic pig, Sus scrofa. Owing to the complex socio-emotional and cognitive abilities of Sus scrofa, we posited that yawn contagion could be present in this species (Prediction 1) and influenced by individual/social factors (Prediction 2). In June-November 2018, on 104 semi-free ranging adolescent/adult pigs, 224 videos were recorded for video analysis on yawning. Kinship information was refined via genetic analyses. Statistical elaboration was conducted via GLMMs and non-parametric/randomization/cross-tabulation tests. We found yawn contagion in Sus scrofa, as it was more likely that pigs yawned when perceiving rather than not perceiving (yawning/control condition) others’ yawns (response peak in the first out of three minutes). Yawn contagion was more likely: (1) in response to males’ yawns; (2) as the age increased; (3) within short distance (1 m); (4) between full siblings, with no significant association between kinship and distance. The influence of kinship suggests that—as also hypothesized for Homo sapiens—yawn contagion might be linked with emotional communication and possibly contagion.